Diagnóstico genético preimplantacional: análisis de aneuploidías únicas - López, Paul W. (2013)
Known causes of unsuccessful pregnancy in couples undergoing assisted reproduction treatment include embryo aneuploidies. Preimplantation genetic diagnosis (PGD) is a technique used in assisted reproduction in order to detect these abnormalities, select embryos chromosomally normal and subsequently transfer to the patients’ uterus. Embryos with single aneuploidies may have the ability to survive and achieve unnoticed implantation. Objectives: To determine incidence of single aneuploidies in good quality embryos in third day of development to blastocyst. Design: Statistical and experimental study. Setting: Reprogenetics Latin-America and Assisted Reproduction Center - Concebir. Biologic material: Samples of embryo biopsies. Methods: Comparative analysis of results from evaluation of each sample obtained by embryo biopsy on the third and fifth days of embryonic development, performing PGD by respectively in situ hybridization (FISH) and comparative genomics (aCGH). Results: On third day of embryonic development 62.9% of embryos with single monosomy had 8-cell morphology. Though when evaluated by aCGH in the blastocyst stage 42.3% were abnormal and 37.5% of these belonged to the 8-cell stage. Single monosomies index in the blastocyst stage was 57.9% in 84.2% of single aneuploidies. Conclusions: Eight-cell embryos on the third day of embryonic development are most likely to reach blastocyst stage and have single aneuploidies.